Assessment of blasting impacts in underwater concrete berth demolition and development of a Hybrid Controlled Blasting (HCB) technique – A case study. (June 2022) - Kumar Modi, Suman; Murthy, V.M.S.R.
Abstract: Expansion of seaports often necessitates demolition of old berths near newly constructed berths. The 'Underwater drilling and blasting' technique is generally preferred for demolition due to higher economy and least dismantling time. The structural vibration in terms of Peak Particle Velocity (PPV) was to be limited below 75 mm/s for the structures located in the proximity as well as 508 mm/s for the connected concrete berth for preventing distress if any. Based on the scaling law established, a Hybrid Controlled Blasting (HCB) technique by redesigning the delays and charge quantities was established. The blast-induced radial crack was also estimated from stress theory to fix the distance between the pre-split hole and line drilling row as 1.5 m for an estimated charge per hole of 2.5 kg. One pre-split hole and two rows of 3 empty holes were drilled in a staggered pattern and blasted to detach the structure safely. The HCB technique helped in successfully screening the structural wave propagation and radial crack beyond the line-drilling row. The vibration progressively reduced from a predicted value of 87.59 mm/s to an actual value of 67.1 mm/s at the monitoring station. The structural strain was also controlled from 1925.4 μmm/mm to less than crack initiation threshold of 1143 μmm/mm at the nearest distance on the adjacent berth. The post-blast survey conducted confirmed that no crack was induced to adjacent berths proving the utility of the technique developed.